2013
DOI: 10.12809/hkmj133930
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop study of leakages across the Portex, TaperGuard and Microcuff Endotracheal tubes under simulated clinical conditions

Abstract: OBJECTIVES. To compare three endotracheal tubes for leakage across the cuff (microaspiration) under a comprehensive set of simulated clinical situations. These were the Mallinckrodt TaperGuard (Covidien, US) with a tapered polyvinyl chloride cuff; the KimVent Microcuff (Kimberly-Clark Health Care, US) with a cylindrical polyurethane cuff; and a conventional Portex (Smiths Medical International Ltd, UK) with a globular polyvinyl chloride cuff. DESIGN. A benchtop experimental study. SETTING AND MATERIALS. A sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…84 Laboratory studies have consistently demonstrated that polyurethane-cuffed ETTs (and similarly designed silicone cuffs) are superior to standard polyvinyl cuffs in minimizing fluid leakage. 70,71,75,[85][86][87] Significantly reduced microaspiration has been reproduced in clinical trials, 75,78 coinciding with significant reductions in VAP (26 -45% relative decrease). [88][89][90] However, others have not been able to demonstrate the superiority of polyurethane-cuffed ETTs in reducing microaspiration.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumonia mentioning
confidence: 89%
“…84 Laboratory studies have consistently demonstrated that polyurethane-cuffed ETTs (and similarly designed silicone cuffs) are superior to standard polyvinyl cuffs in minimizing fluid leakage. 70,71,75,[85][86][87] Significantly reduced microaspiration has been reproduced in clinical trials, 75,78 coinciding with significant reductions in VAP (26 -45% relative decrease). [88][89][90] However, others have not been able to demonstrate the superiority of polyurethane-cuffed ETTs in reducing microaspiration.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumonia mentioning
confidence: 89%
“…Previous evidence suggests that application of PEEP in itself may be lung protective independent of tidal volumes. PEEP may prevent atelectasis [ 41 ], micro-aspiration [ 42 ], and decrease the need for rescue therapies for hypoxia [ 19 ]. Low or absent PEEP may increase shear stress and lung injury independent of the absence of high plateau pressures due to the cyclic collapse and tidal recruitment of lung units referred to as “atelectatrauma” [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our benchtop study showed that the Microcuff consistently outperformed the Portex and the TaperGuard in terms of leakage, especially during zero PEEP mechanical ventilation, laboured breathing, disconnection, and airway suction. 34 One disadvantage of the Microcuff is that the material is so thin that even moisture diffuses across, leading to fluid accumulation inside the cuff with resultant blockage of the pilot balloon tube. This can be solved by purging the tube with small amount of air.…”
Section: Endotracheal Tubementioning
confidence: 99%
“…Without positive pressure, leakage around the cuff is significant, especially if the conventional PVC cuff is used and the cuff pressure is less than 30 cm H 2 O. 34 During routine care, disconnections of the airway circuit are frequent, for instance, use of another ventilator for patient transport, change of the heat-and-moisture exchanger, spontaneous breathing trials, and change of ventilator tubing. Such disconnections should be avoided as far as possible.…”
Section: Airway Pressurementioning
confidence: 99%
See 1 more Smart Citation